A study on the solid image projection mapping system in the curved display of the face shape for the performance art - Seo Song, Eun; Sang Yoo, Gil; Dae Hong, Sung (International Journal of Engineering and Technology, 2018)
Background/Objectives: Aims to study the projection mapping technology which will project the multi-phase solid image in the curved display real time in the performance.Methods/Statistical analysis: Analyze the shape of the object to be mapped for the project and based on the analyzed characteristics, the structure of the installation of the applicable project to the actual object and the projection mapping production tool shall be developed and be applied to the elastic shape.Findings: According to the analysis result of the curved display, one projector did not suit the image and the distortion of the image occurred. According, it was divided into the four sections and projection mapping was made to minimize the problems, and the projection production tool which applied the geometric matching technology, edge blending technology, UDP telecommunication method etc based on the grid for the image matching using the Max/Msp was developed and the actual face shaped curved display was applied.Improvements/Applications: In order to conduct projection map precisely to the actuator moving real time, Z-depth should be considered and the advanced technology which matches the three dimensional mapping image should be applied.Â Â